Strategi Pengajaran Pada Program Linear Untuk Meningkatkan Hasil Belajar Siswa: Systematic Literature Review - raisya, salsabila; Hasbi, Muhammad; Khoirunnisya, Rachael; syabila, Syinta; Yurike, Gabriella Inggrid (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
Linear programming is an essential topic in the high school mathematics curriculum, significantly contributing to students' decision-making and problem-solving skills. However, the complexity of its concepts and applications often becomes a challenge for students, making it challenging for them to translate real-world problems into mathematical models. This study aims to analyze various teaching strategies that have been implemented in linear programming instruction and evaluate their impact on students' learning outcomes. Through a systematic literature review, this study explores differentiated learning,cooperative learning models such as jigsaw, discovery learning, and the integration of technology like GeoGebra. The findings indicate that these methods effectively improve students' understanding and engagement in learning linear programming. By identifying the most effective approaches, this research provides insights for educators to implement better teaching methods, helping students grasp linear programming concepts more comprehensively and confidently.